Guidelines on the management of irritable bowel syndrome - Pietrzak, Anna; Skrzydło-Radomańska, Barbara; Mulak, Agata; Lipiński, Michał; Małecka-Panas, Ewa; Reguła, Jarosław; Rydzewska, Grażyna (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
In memory of Professor Witold Bartnik These guidelines constitute an update of the previous „Recommendations on the management of irritable bowel syndrome” issued in 2008. They have been developed by a Task Force organized by the Governing Board of the Polish Society of Gastroenterology. They discuss, with particular emphasis on new scientific data covering papers published since 2008: the etiology, epidemiology, clinical presentation, diagnostic principles and criteria for the diagnosis, and recommendations for the treatment of irritable bowel syndrome (IBS). The English-language acronym for the syndrome (IBS) has become popular in medical and popular scientific language, it is also widely recognized by patients who identify with this diagnosis. Therefore, in the discussed guidelines, this is what we will use.